Pengaruh Kepemimpinan Kyai dan Etos Kerja Ustadz/Ustadzah terhadap Kompetensi Pengajar di Pondok Pesantren Qotrun Nada Kota Depok - Humaidi Mufa; Mohamad Jaenudin; Amie Primarni (Jurnal Dirosah Islamiyah, 2019)
The purpose of this study is; (1) To study and analyze the influence of clerical leadership and the workethic of cleric / cleric to the professional competence of teachers at the Qotrun Nada Islamic BoardingSchool Depok jointly, (2) the influence of the cleric leadership on the Teacher Competence at the QotrunNada Islamic Boarding School in Depok, (3) the influence of the work ethic of the cleric / cleric to theTeacher Competence at the Qotrun Nada Islamic Boarding School in Depok, (4) which is more influentialbetween the clerical leadership or the work ethic of the cleric / cleric to the Teacher Competence at theQotrun Nada Islamic Boarding School in Depok.The method used in this research is quantitative descriptive method. The sample taken is the wholepopulation. The data analysis technique used is multiple linear regression analysis.From the results of the study it was found that the influence of the kyai's leadership on TeacherCompetence at Qotrun Nada Islamic Boarding School was not too significant. This is evidenced by the ttest value, sig value of 0.136 <0.05 then Ho is accepted and Ha is rejected. There is an influence of ustadz/ ustadzah's work ethic on Teacher Competence at Qotrun Nada Islamic Boarding School. This isevidenced by the t test value, sig value 0,000 <0.05 then Ho is rejected and Ha is accepted. The leadershipof the kya and the work ethic of the cleric / cleric contributed concurrently to the Teacher Competence atQotrun Nada Islamic Boarding School at 52.8%, this was evidenced by the f test.Keywords: clerical leadership, teacher competence, work ethic.